Mezi gens a regnum. Církev a její role na pomezí krize tradiční společnosti a vznikem raně středověkého státu [Between Gens and Regnum. The Church and Its Role in the Transition Through a Crisis of Traditional Society to the Beginning of an Early Medieval State] - Václav Drška (Mediaevalia Historica Bohemica, 2021)
The article continues the ongoing debate about a “pre-state” tribal society and the nature of its transformation into an early medieval “state” (regnum). The methodological approach is to understand this transformation as an institutional crisis within the tribal society. The opportuni-ties to detect the key moments of this process are tested on the narrative strategies of medieval chroniclers based on the expectation that creating Christian monarchic power took place under the control of the church that tried to influence its form to correspond to the characteristics of the given patrician tradition. It also benefits from the reality that the authors of these texts were clergymen for whom this idea was natural. Using comparative examination, it seeks out typical testimonies that can be considered traditional locations of literary memory of communication between the sovereign and the tribe. In this way, the study attempts to define the basic strategy the sovereign employed to subjugate “their” people within the framework of Christian ethical discourse.